The meaning of innovation in the umrah business process: A qualitative study on umrah travel - Nur’Syamsiyah, Hidayatul; Manafe, Leonard Adrie; Nugroho, Dodit Cahyo (Privietlab, 2025)
This study focuses on examining the integrative factors that determine successful innovations in the business process of Umrah in PT. Umi Muthmainah Berkah Umrah and Hajj Travel are located in Surabaya. The factors examined were technology, regulation, human resource (HR) quality, and pilgrims' trust. The method used was qualitative, with a case study approach and data collection through in-depth interviews, observations, and document analysis. The results showed that while digitized systems bolster operational efficiency and convenience for pilgrims, a far greater hurdle in human resources limits the ability to utilize technology. Travel companies are subject to strict compliance requirements, which necessitate continual adaptation and travel agency innovation. The human resource quality gained through systematic and ongoing training fosters successful innovation, while trust from pilgrims significantly affects business reputation and sustainability. This study affirms the synergistic integration of technology, regulation, human resources, and congregation trust, which constitute the pillars of innovation and umrah business success. The study results suggest directions for management to focus more on the enhancement of technology and human resources, and for the government to formulate pro-innovation policy regulations. This study also encourages the public to be more discerning in selecting a Umrah bureau to receive optimal and more trustworthy services.